Correlation of Free Fire Online Game Playing Intensity with Elementary School Students' Social and Emotional Intelligence - Delila Nur Hamidah; Murfiah Dewi Wulandari (FKIP - Universitas Riau, 2026)
This study aims to know the relationship between the intensity of playing the online game Free Fire with the social intelligence and emotional intelligence of elementary school students. The method used is a quantitative approach with a correlational design (ex post facto). The study population included all students in grades III to VI at SD Negeri 1 and SD Negeri 3 Bangkleyan, with a sample size of 200 students determined through a total sampling technique. Data were collected using a closed-ended Likert-scale questionnaire that had been tested for validity and reliability. Data analysis included descriptive statistics, the Kolmogorov–Smirnov normality test, and the Spearman Rho correlation test using SPSS. The results of the normality test showed that the data were not normally distributed. The correlation analysis showed a positive and significant relationship between the intensity of playing Free Fire with social intelligence (r = 0.707; p < 0.05) and emotional intelligence (r = 0.657; p < 0.05) with a strong relationship level. These findings emphasize the importance of the role of parents and teachers in supervising gaming activities to have a positive impact on children's development.